2017
DOI: 10.3201/eid2308.161358
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus and Other Respiratory Viral Infections during Pregnancy and Birth, Nepal

Abstract: Women infected with human metapneumovirus during pregnancy had an increased risk of delivering infants who were small for gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…72 The median duration of maternal symptoms in a study from Nepal was 5 days, and almost one-half (43.6%) of pregnant women with hMPV also had a viral co-infection, most frequently due to rhinovirus and followed by coronavirus and parainfluenza. 69 Birth outcomes in the Nepal study revealed no differences in birthweight or frequency of premature delivery between infants from pregnant mothers with and without hMPV infection. However, women having hMPV infection during pregnancy were 1.7 times (P=.03) more likely to have a small-for-gestational age newborn compared with uninfected women.…”
Section: Metapneumovirus (Hmpv)mentioning
confidence: 82%
See 1 more Smart Citation
“…72 The median duration of maternal symptoms in a study from Nepal was 5 days, and almost one-half (43.6%) of pregnant women with hMPV also had a viral co-infection, most frequently due to rhinovirus and followed by coronavirus and parainfluenza. 69 Birth outcomes in the Nepal study revealed no differences in birthweight or frequency of premature delivery between infants from pregnant mothers with and without hMPV infection. However, women having hMPV infection during pregnancy were 1.7 times (P=.03) more likely to have a small-for-gestational age newborn compared with uninfected women.…”
Section: Metapneumovirus (Hmpv)mentioning
confidence: 82%
“…63,[65][66][67] Human metapneumovirus causes approximately 5 to 25% of all respiratory in infants and children, and is responsible for between 5 and 15% of childhood hospitalizations for lower respiratory tract disease. [68][69][70] The infection is so prevalent that virtually all children will have been infected with hMPV by the time they reach 5 years of age. 71 There are little data available on hMPV during pregnancy.…”
Section: Metapneumovirus (Hmpv)mentioning
confidence: 99%
“…In a region of the world with limited access to medical care, this was a notable finding. Additionally, rhinovirus and human metapneumovirus infections with fever and respiratory symptoms during pregnancy both were found to be associated with increased risk of fetal growth restriction, manifested as low birth weight or small-for-gestational-age births [21]. Overall, these studies demonstrate that respiratory viral infections during pregnancy may adversely affect maternal and fetal outcomes.…”
Section: Concepts Of Maternal Immunizationmentioning
confidence: 73%
“…In South Africa, RSV prevalence based on the presence of respiratory symptoms was much higher at 2%, or an incidence of 14.4-48.0 cases per 1000 person-years overall [20]. Rhinovirus, coronavirus, parainfluenza viruses 1-4, and human metapneumovirus have also recently been detected in cases of respiratory viral infections in pregnant women [21,22]. Rhinovirus is described as a cause of influenza-like illness in several studies in pregnant women, and Middle Eastern Respiratory Syndrome and Severe Acute Respiratory Syndrome coronaviruses have been shown in case reports to be associated with severe disease in pregnant women [23,24].…”
Section: Concepts Of Maternal Immunizationmentioning
confidence: 99%
“…Only recently was respiratory syncytial virus infection shown to result in severe respiratory disease and hospitalization, as reported by a case-series study [10]. In addition, human metapneumovirus (HMPV) infection and febrile human rhinovirus (HRV) infection in mothers have been associated with infants that are small for gestational age and infants with a low birth weight, respectively [11,12].…”
mentioning
confidence: 99%